2021
DOI: 10.1101/2021.03.20.436288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CSF1R inhibitor levels determine sex-specific phenotype of resilient microglia and neurofunctional rescue leading to extended survival in tauopathy mice

Abstract: Microglia are a fundamental component of pathogenesis in many neurological conditions and have specialized functions that vary by disease stage or specific pathology. Drugs targeting colony-stimulating factor-1 receptor (CSF1R) to block microglial proliferation in preclinical disease models have shown mixed outcomes, thus the therapeutic potential of this approach remains unclear. Here, we evaluated CSF1R inhibitors in tauopathy mice using multiple dosing schemes, drug analogs, and longitudinal measurements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 105 publications
(181 reference statements)
0
6
0
Order By: Relevance
“…We found that the SPP1-positive microglia state can be selectively depleted by genetic and pharmacological inhibition of CSF1R. CSF1R inhibitors have beneficial effects in mouse models of diseases including AD 69,70 , tauopathy 60 and MS 71 . Intriguingly, CSF1R inhibition reduced SPP1 expression in the MS model, while homeostatic genes such as TMEM119 and P2RY12 were increased 71 , paralleling our finding that the SPP1 microglia state is selectively vulnerable to CSF1R inhibition.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…We found that the SPP1-positive microglia state can be selectively depleted by genetic and pharmacological inhibition of CSF1R. CSF1R inhibitors have beneficial effects in mouse models of diseases including AD 69,70 , tauopathy 60 and MS 71 . Intriguingly, CSF1R inhibition reduced SPP1 expression in the MS model, while homeostatic genes such as TMEM119 and P2RY12 were increased 71 , paralleling our finding that the SPP1 microglia state is selectively vulnerable to CSF1R inhibition.…”
Section: Discussionmentioning
confidence: 88%
“…Based on these results of genetic perturbations, we asked if pharmacological targeting of the same hits would similarly modulate the abundance of the SPP1+ state. Indeed, inhibition of MAPK14 with Skepinon-L increased the fraction of SPP1+ microglia in a time-dependent manner at nontoxic concentrations (Fig 7i,j) Given that pharmacological inhibition of CSF1R has shown beneficial effects in several neurodegenerative mouse models, and was observed by us and others to selectively affect subpopulations of microglia in mice [63][64][65] , we tested if pharmacological inhibition of CSF1R would reduce the proportion of SPP1+ microglia. While the CSF1R inhibitor PLX3397 showed dose-dependent toxicity in iTF-Microglia (Fig.…”
Section: Crop-seq Uncovers Regulators Of Microglial Cell Statesmentioning
confidence: 96%
See 1 more Smart Citation
“…At this stage, GM-CSF may act to maintain microglia in a non-activated state, promote anti-inflammatory cytokine expression, and reduce pro-inflammatory cytokine expression (Ahmed et al, 2021 ; Potter et al, 2021 ). CSF1R inhibitors may also be beneficial at this stage to reduce the numbers of activated microglia while maintaining quiescent microglia that play important roles in immune surveillance and brain homeostasis (Johnson et al, 2021b ). The clinical dementia stage is characterized by neurodegeneration due to widespread NFT formation and chronic neuroinflammation that persists through the mid-40s, 50s, and 60s, during which a majority of individuals with DS have clinical dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, in mouse models of primary tauopathy, characterized by inclusions of the protein tau in neural cells (Kovacs, 2015 ), CSF1R inhibitors reduced pathological tau aggregation and subsequent neurodegeneration (Mancuso et al, 2019 ; Shi et al, 2019 ). However, recent evidence suggests that complete microglial depletion is neither necessary nor desirable for extending lifespan in tauopathy mice and that microglia resilient to CSF1R inhibition exist in a quiescent, non-activated state and may serve important roles in prevention and recovery from tau-induced neurodegeneration (Johnson et al, 2021b ). Together, these studies underscore the importance of carefully considering microglial state and function over the disease course in order to appropriately balance microglial stimulation and repression therapeutically.…”
Section: Introductionmentioning
confidence: 99%